ETNOZOLOOGI UNTUK RITUAL ADAT MASYARAKAT DAYAK KAYAAN DI DESA PADUA MENDALAM KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Mering, Marcelius; Anwari, M Sofwan; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2019)
The local People of Kalimantan until now still depend on nature, they uilize flora and fauna for daily needs. Dayak Kayaan community in Padua Mendalam Village, Putussibau Utara District, Kapuas Hulu Regency have diversity in the utilization of animal Species including the use of animals for traditional rituals. The purpose of this study was to collect data of animals species that used for traditional rituals Dayak Kayaan people in Padua Mendalam Village, Putussibau Utara District, Kapuas Hulu District. Data collection with survey method and interviews with selected respondents using snowball sampling technique. The results there were 9 species from 9 families, every species of family consisted of only 1 species. The body parts used for traditional rituals are blood, the whole body, tail, head, feathers an shells. How to use every part of the body has a difference depending on the type of traditional rituals performed.Keyword : Ethnozoology For Traditional Rituals Community Dayak Kayaan.